2020
DOI: 10.3389/fcell.2020.00352
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Biomaterial Implant Wear Debris on Osteoblasts

Abstract: Aseptic loosening subsequent to periprosthetic osteolysis is the leading cause for the revision of arthroplasty failure. The biological response of macrophages to wear debris has been well established, however, the equilibrium of bone remodeling is not only dictated by osteoclastic bone resorption but also by osteoblast-mediated bone formation. Increasing evidence shows that wear debris significantly impair osteoblastic physiology and subsequent bone formation. In the present review, we update the current stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 178 publications
2
70
0
Order By: Relevance
“…However, AL accompanied by PPOL is one of the main factors that resulted in TJA failure ( Abu-Amer et al, 2007 ). The mechanism of wear particle-induced periprosthetic osteolysis has not been fully understood to date, osteoclast-mediated bone resorption has been identified as the primary driver for this process ( Masui et al, 2005 ; Goodman and Gallo, 2019 ; Zhang et al, 2020 ). Suppression of osteoclastic activation is a key to preventing wear-particles induced PPOL ( Goodman and Gallo, 2019 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, AL accompanied by PPOL is one of the main factors that resulted in TJA failure ( Abu-Amer et al, 2007 ). The mechanism of wear particle-induced periprosthetic osteolysis has not been fully understood to date, osteoclast-mediated bone resorption has been identified as the primary driver for this process ( Masui et al, 2005 ; Goodman and Gallo, 2019 ; Zhang et al, 2020 ). Suppression of osteoclastic activation is a key to preventing wear-particles induced PPOL ( Goodman and Gallo, 2019 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 55% of hip ( Sadoghi et al, 2013 ) and 31% of knee ( Sharkey et al, 2014 ) revisions are caused by AL accompanied by PPOL. Wear particles after TJA, such as polyethylene, titanium, and polymethyl methacrylate, can attract the recruitment of macrophages along with other cells, which produce chemokines, cytokines, and other pro-inflammatory components that sustain chronic inflammation, inducing osteoclastic differentiation and bone resorption ( Goodman and Gallo, 2019 ; Zhang et al, 2020 ). Furthermore, it’s reported that these factors have been investigated under the periprosthetic milieu ( Masui et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of implant surface changes can help to clarify the mechanisms and dynamics behind the elution of Ti in the body, which remains unclear at the time of writing, in order to further explain the potential mechanisms of dental implant degradation and their relation to peri-implant diseases [ 31 ]. The rationale is that leached particles can be phagocytosed by macrophages and release mediators of inflammation, which can potentially inhibit osteoblast formation, leading to bone resorption and, ultimately, the clinical loosening of implants [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, implant D showed a surface contamination with the presence of alumina particles (Figure 8), the latter being residues from the sandblasting finishing step. Its diffusion in the peri-implant bone surface may produce biological perturbations such as the inhibition of bone mineralization, the activation of osteoclast-like cells, and the enhancement of the bone erosion [52,53]. Bertoldi et al evidenced the association between the Al wear particles with oxidative and inflammatory reactions, including iron-mediated oxidation [54].…”
Section: Discussionmentioning
confidence: 99%